Determinación de indicadores de contaminación fecal (coliformes fecales) en los tanques de abastecimiento de agua de la Universidad Distrital Francisco José de Caldas Sedes Macarena a y b - Poveda O, Miguel D.; Beltrán, Héctor E.; Giraldo, Gustavo (Revista Científica, 2011)
This research determined the water quality coming from the supply tanks and the Faculty of Education headquarters Macarena A and B, belonging to the University District. It took eight sampling points in the two sites, with priority to the bathroom taps and water tanks. In the laboratory, we used the membrane filtration technique and Chromocult Agar selective medium for detecting the presence of fecal coli- forms. The results for physico-chemical parameters of water presented to the pH levels between 7.2 to 7.5, nitrate, nitrite, phosphate, ammonium were zero (0 ppm), and dissolved oxygen was maintai- ned between 8.5 and 9mg / L., which showed that the water is fit for human consumption. However, it is necessary to take preventive measures for the proper use of physical space in the sink and faucets for direct access to drinking water.